2021
DOI: 10.1371/journal.pone.0256984
|View full text |Cite|
|
Sign up to set email alerts
|

Combined application of zinc and silicon alleviates terminal drought stress in wheat by triggering morpho-physiological and antioxidants defense mechanisms

Abstract: Wheat is an important global staple food crop; however, its productivity is severely hampered by changing climate. Erratic rain patterns cause terminal drought stress, which affect reproductive development and crop yield. This study investigates the potential and zinc (Zn) and silicon (Si) to ameliorate terminal drought stress in wheat and associated mechanisms. Two different drought stress levels, i.e., control [80% water holding capacity (WHC) was maintained] and terminal drought stress (40% WHC maintained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…Water stress is the major limiting factor responsible for the reduced growth and yield of crops (Sattar et al 2021). Results obtained from our study showed all the growth attributes i.e., shoot and root length, plant fresh and dry biomass, as well as yield parameters, showed signi cant reduction after exposure to water stress in both canola cultivars.…”
Section: Discussionmentioning
confidence: 51%
“…Water stress is the major limiting factor responsible for the reduced growth and yield of crops (Sattar et al 2021). Results obtained from our study showed all the growth attributes i.e., shoot and root length, plant fresh and dry biomass, as well as yield parameters, showed signi cant reduction after exposure to water stress in both canola cultivars.…”
Section: Discussionmentioning
confidence: 51%
“…As it is known, if the plant height is getting higher, it increases surface evaporation and also the loss of water. Similarly, several researchers reported that drought stress has inhibitory effects on plant growth and decreases the shoot and root fresh weight (Sattar et al, 2021, Rafique et al, 2022. Water deficit decreased seed GR and seed germination percentage.…”
Section: Resultsmentioning
confidence: 86%
“…This was confirmed in another study [ 56 ]. Osmotic variability due to variations in osmotic potential caused a significant decrease in the fresh weight of plants due to a decrease in cellular division, consequently causing a decrease in total plant weight [ 57 ]. Zn combined with AMF treatment effectively improved plant growth under drought stress by sustaining higher water content in cells, thus ameliorating drought stress.…”
Section: Discussionmentioning
confidence: 99%